Heavy metal depuration in flat tree oysters Isognomon alatus under field and laboratory conditions - Saed, Katayon; Ismail, Ahmad; Omar, Hishamuddin; Kusnan, Misri (Taylor & Francis, 2004)
Oysters Isognomon alatus containing high concentrations of Zn, Cu, Pb and Cd were collected from the Sepang Besar River, and transferred to the Sepang Kecil River where the native oysters contain low metal concentrations. Concentrations of heavy metals in oysters were measured monthly over six months. The concentrations of all metals decreased significantly (p < 0.05) for Cd 87%, Pb 83%, Cu 78%, and Zn 59%. In addition, metal depuration in oysters was investigated under laboratory conditions. Oysters were exposed to 100 μg g-1 of metals for two weeks followed by one week of depuration. Our studies suggest that metals in oysters tend to be lost in the order, Cd > Pb > Cu > Zn. A comparison between laboratory and field data showed that depuration of metals under the laboratory conditions is significantly faster than in the field.